Training in realistic virtual environments: Impact on user performance in a motor imagery-based Brain-Computer-Interface - Silva-Sauer, Leandro; Valero-Aguayo, Luis; Velasco-Álvarez, Francisco Javier; Varona-Moya, Sergio; Ron-Angevin, Ricardo (My University, 2015)
A brain–computer interface (BCI) is a system that enables people to control an external device by means of their brain activity, without the need of performing muscular activity. BCI systems are normally first tested on a controlled environment before being used in a real, daily scenario. While this is due to security reasons, the conditions that BCI systems users will eventually face in their usual environment may affect their performance in an unforeseen way. In this paper, we try to bridge this gap by presenting a trained BCI user a virtual environment that includes realistic distracting stimuli and testing whether the complexity or the type of such stimuli affects user performance. 11 subjects navigated two virtual environments: a static park and the same one with visual and auditory stimuli simulating typical distractors from a real park. No significant differences were found when using a realistic environment; in other words, the presence of different distracting stimuli did not worsen user performance.
Keywords: Redes neuronales (Informática); Brain Computer Interface; Virtual Reality; User performance; Motor imagery